The genetics of a small autosomal region of Drosophila melanogaster containing the structural gene for Alcohol dehydrogenase. - Ashburner, M. (Genetics, 1982)
A lethal locus (l(2)br7;35B6-10), near Adh on chromosome arm 2L of D. melanogaster, is identified with Plunkett's dominant suppressor of Hairless (H). Of eight new alleles, seven act as dominant suppressors of H, the eighth is a dominant enhancer of H. One of the suppressor alleles is both a leaky lethal and a weak suppressor of H. Confirming Nash (1970), deletions of l(2)br7 are dominant suppressors, and duplications are dominant enhancers of H. A simple model is proposed to account for the interaction of l(2)br7 and H, assuming that amorphic (or hypomorphic) alleles of l(2)br7 suppress H and that hypermorphic alleles enhance H.